2016
DOI: 10.3892/ol.2016.4640
|View full text |Cite
|
Sign up to set email alerts
|

Incidental and non-incidental thyroid microcarcinoma

Abstract: Abstract. There is no clear therapeutic approach for thyroid microcarcinoma (TMC). This may be as a consequence of recent observations that have reported biologically different types of TMC, which should be treated differently. The objective of the present study was to compare incidental TMC (ITMC) and non-incidental TMC (NITMC) in order to assess the differences in the incidence, diagnostic results, clinicopathological characteristics and surgical treatment. The study consisted of a retrospective chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
2
20
1
2
Order By: Relevance
“…The median size of the cancer foci in the NITC group was larger than the ITC group, and the majority of the cancer foci in ITC group was microcarcinoma. In the majority of the previous studies, it was shown that the size of ITC was smaller than NITC . In our study, only five tumor foci were greater than 1 cm in the ITC group.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…The median size of the cancer foci in the NITC group was larger than the ITC group, and the majority of the cancer foci in ITC group was microcarcinoma. In the majority of the previous studies, it was shown that the size of ITC was smaller than NITC . In our study, only five tumor foci were greater than 1 cm in the ITC group.…”
Section: Discussioncontrasting
confidence: 48%
“…In the majority of the previous studies, it was shown that the size of ITC was smaller than NITC. 2,17,18 In our study, only five tumor foci were greater than 1 cm in the ITC group. The rarity of ITC larger than 1 cm can be explained by routine evaluation of the majority of the nodules greater than 1 cm by FNA.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The results of the study revealed that either LT-accompanied PTCs or MNH-accompanied IPTCs were more common than solely IPTCs. Yet, IPTCs with MNH were more common than IPTCs with LT [14,34]. In the present study, LT was defined as the presence of lymphocytic infiltrate with lymphoid follicles and oncocytic metaplasia in follicular epithelial cells regardless of the status of serum antibodies, and we ignored focally lymphocytic infiltrates during the assessment.…”
Section: Discussionmentioning
confidence: 99%